Differences in habitat suitability for Sphaeriidae (Mollusca: Bivalvia) according to survey method using probability distribution models - Jeong-Ki Min; Gyoung Min Cho; Jin-Young Kim (Journal of Freshwater Ecology)
Despite the ecological importance of Sphaeriidae, habitat preferences of Pisidium coreanum and Musculium lacustre in the Republic of Korea remain poorly understood. This study evaluated habitat suitability of both species using two distinct datasets: a targeted fingernail clams survey (58 samples, 2023) and a national biological monitoring program (20,580 samples, 2012–2021). Using twelve probability distribution models (PDMs), including reversed log-normal and Weibull distributions, we derived habitat suitability indices (HSIs) four environmental variables—altitude, water depth, velocity, and mean substrate particle size. Optimal habitat ranges varied notably between surveys: P. coreanum showed thermophobic, rheophobic, and lithophobic traits in the fingernail clams survey but thermophilic, rheophilic, and lithophilic characteristics in the biomonitoring data. Similarly, M. lacustre also displayed variation in habitat traits across datasets. These contrasting ecological profiles reflect methodological differences between surveys: targeted multi-habitat sampling in the fingernail clams survey versus riffle-focused sampling in the biomonitoring program. Our results demonstrate that habitat suitability assessments are sensitive to survey design, potentially leading to conflicting interpretations of species’ ecological niches. Furthermore, combining closely related species (e.g. at the family level) without considering such variation may obscure species-specific habitat signals, especially for small, passively dispersed bivalves like Sphaeriidae. This study provides a framework for applying PDMs in habitat modeling and highlights the importance of aligning data sources with ecological research or conservation goals. Method-aware habitat characterization is essential for improving indicator development, refining conservation strategies, and enhancing interpretation of benthic macroinvertebrate monitoring data.